(3)3x-4+9=6

Simple and best practice solution for (3)3x-4+9=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3)3x-4+9=6 equation:


Simplifying
(3) * 3x + -4 + 9 = 6

Multiply 3 * 3
9x + -4 + 9 = 6

Reorder the terms:
-4 + 9 + 9x = 6

Combine like terms: -4 + 9 = 5
5 + 9x = 6

Solving
5 + 9x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 9x = 6 + -5

Combine like terms: 5 + -5 = 0
0 + 9x = 6 + -5
9x = 6 + -5

Combine like terms: 6 + -5 = 1
9x = 1

Divide each side by '9'.
x = 0.1111111111

Simplifying
x = 0.1111111111

See similar equations:

| 32+b=42 | | -220x+7208=0 | | -14=2.5(9-2b) | | .25x-1.5y=6 | | -30-5n=2(-6n+6) | | n+14=73 | | -9x+3=4x+10 | | 80x+320=0 | | (11x+2)(8x+7)= | | 80x+320=-220x+7208 | | -6v+2=-6v-4 | | 60+5y=80 | | -15+7x=33-4x | | 3x^2-6=-3 | | 4x+4(x+2)=48 | | Inx+In(x-6)=5 | | x^2-25x-9350=0 | | 30-5x=-6-24 | | 24+17+b=56 | | x^2+3x=1.5 | | 4(x-4)+3=2x-1 | | x^2+y^2=13 | | -1fith*y=10 | | (x+2)(x-2)=2 | | 5m+2(1m+1)=23 | | (x+2)(x-2)=10 | | (x+2)(x-2)=4 | | (x+2)(x-2)=6 | | 7(1-9)=-3(5+3q) | | 6x-7y=19 | | 4+35=360 | | (x+2)(x-2)=8 |

Equations solver categories